Reporte de Úlcera Corneal por Traumatismo en Bovino y Enucleación Durante la Pasantía de Clínica de Bovinos en el Municipio Zipaquirá, Cundinamarca, Colombia - Cano Rojas, Daniela Stefanny; Castro Madrigal, Daniela (Universidad Antonio Nariño, 2023)
We carry out internships in Zipaquirá, a municipality located in Cundinamarca; we had the opportunity to accompany Doctor Herbert Camargo doing different activities in the bovine area. Mainly, gestational checks, heat synchronization through devices and artificial insemination (AI) were carried out, in addition, owners and administrators of various farms were advised seeking to improve milk quality and mastitis degrees, speaking of purely dairy herds; likewise reviewing the feeding, control and prevention of endogenous and exogenous parasites in animals; suggest the administration of vitamins in animals that need it and ensure that they are up-to-date with mandatory vaccinations.